Penerapan Metode Backward Chaining untuk Mendiagnosa Gangguang pada Tanaman Padi (Studi kasus di Subdistrik Natarbora Timor-Leste) - Louvareto Costa Câmara; Rina Dewi Indah Sari (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
Rice cultivation has many challenges, including disease disorders in rice plants. This study aims to help rice farmers diagnose disease disorders in rice plants using an expert system. This system will display the results of the diagnosis in the form of the name of the disease, description of disease solutions and prevention. There are 5 diseases with 16 symptoms discussed. The knowledge base was built from the 5-disease data, then an isolation diagram of the problem area of rice plant disturbance was made, determination of decision targets and dependency diagrams were made. The establishment of IF–THEN rules use a decision table which consists of a complete table and a reduction table. Inference is carried out using the backward chaining method which begins with the determination of GOAL, namely diseases in rice plants that have 6 values (attribute values). The inference process involves a stack data structure for GOAL and a queue for queue rules. Budidaya tanaman padi memiliki banyak tantangan diantaranya adalah gangguan penyakit pada tanaman padi. Penelitian ini bertujuan untuk membantu petani tanaman padi mendiagnosa gangguan penyakit pada tanaman padi menggunakan sistem pakar. Sistem ini akan menampilkan hasil diagnosa berupa nama penyakit, keterangan penyakit solusi dan pencegahannya. Terdapat 5 penyakit dengan 16 gejala yang dibahas. Basis pengetahuan dibangun dari 5 data penyakit tersebut, kemudian dibuatlah diagram isolasi area permasalahan gangguan tanaman padi, penentuan target keputusan dan diagram ketergantungan. Pembentukan aturan (rule) IF–THEN menggunakan decision tabel yang terdiri dari complete table dan reduction table. Inferensi dilakukan menggunakan metode backward chaining yang diawali dengan penentuan GOAL yaitu penyakit pada tanaman padi yang memiliki 6 value (nilai atribut). Proses inferensi melibatkan struktur data stack untuk GOAL dan queue untuk antrian rule.